Membangun Budaya Knowledge Sharing sebagai Upaya Pencegahan Perilaku Knowledge Hiding pada Dosen - Ulfa, Adilla Kustya; Mujib, Miftachul; Kusuma, Pradana Jati; Sari, Raden Ayu Aminah Rizkia Puspita (Jurusan Akuntansi Politeknik Negeri Pontianak, 2023)
This research examines the influence of knowledge-sharing culture in higher education institutions on knowledge-hiding behavior in lecturers. Second, we tested the influence of ethical leadership on knowledge-hiding behavior in lecturers. This research was designed as explanatory research with a quantitative approach. The population in this study were all lecturers spread throughout Indonesia, with a sample size of 150 people. The data collection technique uses a survey method by distributing questionnaires to respondents. Data analysis was carried out using validity and reliability tests. Hypothesis testing used the Structural Equation Model (SEM) technique with the Partial Least Square (PLS) approach. The results of data analysis prove H1 and H2, where a culture of knowledge sharing and ethical leadership has a negative effect on knowledge hiding. The research results contribute to developing literature on knowledge hiding, especially in higher education. These results also contribute practically, especially to higher education institutions, in anticipating the emergence of the knowledge-hiding phenomenon among lecturers.